2012
DOI: 10.1002/ccd.23048
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast medium volume to creatinine clearance ratio: A predictor of contrast‐induced nephropathy in the first 72 hours following percutaneous coronary intervention

Abstract: A V/CrCl ratio > 2.62 was a significant and independent predictor of CIN after PCI in unselected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 21 publications
4
46
1
4
Order By: Relevance
“…Reported CIN frequency (sCR rise ≥44.2 μmol and/or 25% from baseline) at g-I/eGFR ratios <1.0 in the PCI studies were ≤3% [3,13,14,26,27] and mean g-I/GFR ratios in patients without and with CIN ranged between 0.7-1.0 and 1.2-1.8, respectively [13,15,23,27]. Although no such studies based on individual patients exist regarding CM-enhanced CT, pooled analysis of CT studies reporting mean data of g-I dose (or mean volume and concentration) and eGFR demonstrates a weighted mean CIN risk of 6% at a weighted mean g-I/eGFR ratio of 0.9 (Table 1).…”
Section: Contrast Medium Dose/gfr Ratio As a Predictor Of Cinmentioning
confidence: 98%
See 1 more Smart Citation
“…Reported CIN frequency (sCR rise ≥44.2 μmol and/or 25% from baseline) at g-I/eGFR ratios <1.0 in the PCI studies were ≤3% [3,13,14,26,27] and mean g-I/GFR ratios in patients without and with CIN ranged between 0.7-1.0 and 1.2-1.8, respectively [13,15,23,27]. Although no such studies based on individual patients exist regarding CM-enhanced CT, pooled analysis of CT studies reporting mean data of g-I dose (or mean volume and concentration) and eGFR demonstrates a weighted mean CIN risk of 6% at a weighted mean g-I/eGFR ratio of 0.9 (Table 1).…”
Section: Contrast Medium Dose/gfr Ratio As a Predictor Of Cinmentioning
confidence: 98%
“…This ratio has during recent years been studied with the goal of defining a threshold value for the risk of CIN in PCI [13][14][15][23][24][25][26][27]. Analysis of these studies demonstrates a weighted mean g-I/eGFR value >1.2 to be a significant and independent predictor of CIN (Table 2).…”
Section: Contrast Medium Dose/gfr Ratio As a Predictor Of Cinmentioning
confidence: 99%
“…3,4 Several previous studies have investigated the predictive value of the ratio of contrast media volume-to-creatinine clearance (V/CrCl) for CIN after percutaneous coronary intervention (PCI). 5,6 A V/CrCl value >3.7 was found to be a significant independent predictor of an early (within 24 hour) abnormal increase in serum creatinine after PCI in a group of consecutive patients; this became 1 recommended method for evaluating the safe maximum volume of contrast. 5 Studies from our group also indicated that V/CrCl >2.62 was a significant and independent predictor of CIN (within 48-72 hour) in consecutive patients undergoing PCI.…”
mentioning
confidence: 96%
“…al) to >6.15 (Barbieri et. al) (14) (15) . These data are not strictly comparable with those reported in the current study because of the differences in the total number of the patients studied, the number of patients with chronic kidney disease, the definition of CIN and the overall incidence of CIN.…”
Section: Cin Has Been a Bane Of Interventional Cardiologymentioning
confidence: 99%